Acoustic field switching of piezoelectric device for microsphere diameter sorting. (15th February 2023) - Feng, Haoren; Wang, Liang; Yan, Xuran; Jin, Jiamei; Zhao, Chunsheng
Highlights: Non-destructive diameter sorting of the ICF microsphere was realized by switching the acoustic fields. The distribution characteristics of the acoustic field generated by the elastomer vibration were obtained by theoretical analysis. The ICF microspheres with a diameter of 480 μm and 680 μm were sorted within 13 s by controlling the electrical signal applied to the piezoelectric plates. Abstract: To realize non-destructive diameter sorting of the inertial confinement fusion (ICF) microspheres, a novel standing waves piezoelectric sorting device is proposed in this study. Six piezoelectric plates and a container constitute the proposed device. The piezoelectric plates are used to excite the standard second-order bending vibration mode and the non-standard fourth-order bending vibration mode of the container, respectively, thereby two standing waves are produced in the liquid inside the container. Adjusting the working sequence and working duration of the two standing waves to realize the sorting of the ICF microspheres with different diameters. First, the distribution characteristics of the acoustic field produced by the vibration mode are theoretically analyzed. Then, the finite element method is used to analyze the vibration modes of the proposed device and the induced acoustic fields, optimize its dimensions, and verify the feasibility of the proposed sorting principle. In addition, vibration tests are performed on the prototype of the proposed device to analyze its vibration characteristics. Finally, an experimental platform is built to conduct the manipulation and sorting tests for the ICF microspheres. Experimental results show that the maximum average velocities of the ICF microsphere driven by the two vibration modes are 1.49 mm/s and 3.93 mm/s, respectively. And the difference in moving velocity caused by the difference in their diameter is significant. By controlling the excitation signals, the ICF microspheres with diameters of 480 μm and 680 μm can be effectively sorted within 13 s. The proposed standing wave piezoelectric sorting device holds the advantages of non-contact, non-destructive, cross-scale manipulation, and easy manufacturing, presenting the potential application for sorting the ICF microspheres and improving the detection efficiency. Graphical Abstract: Image, graphical abstract